Astaxanthin alleviates palmitic acid‐induced hindrance of porcine oocyte maturation. Issue 11 (7th August 2022) - He, Xu; Wang, Dayu; Zhu, Fuquan; Jiang, Yuan; Bi, Jiaying; Lu, Xinyue; Zhao, Mingyue; Wu, Weidong; Li, Juan
Abstract: Increased palmitic acid (PA) levels have been found in females with reduced fertility due to metabolic disorders. However, effective antioxidant astaxanthin (AXE) might positively affect animal reproduction. Therefore, the present study was designed to evaluate the impact of a high concentration of PA on oocyte maturation and the possible protective effect of AXE against high PA concentration in pigs. Firstly, different concentrations (0.2, 0.5, 0.8 mM) of PA were conducted on in vitro maturation (IVM) of pig oocytes (PA0.2, PA0.5, and PA0.8), while no addition of PA was performed as the control group (Ctrl). Results showed that the cumulus cell expansion index (CCEI) was lower in PA0.5 and PA0.8 groups compared to Ctrl group ( p < .05). In PA0.5 group, not only did the percentage of matured oocytes with the first polar body (PB1) reduced, that with more oocytes arrested at germinal vesicle (GV) stage (53.44% ± 7.16% vs. 20.93% ± 5.16%, p < .05), but also a higher number of transzonal projections (TZPs) was observed in PA0.5 than Ctrl group. Besides, supplement of PA resulted in a dose‐dependent decrease in mitochondrial activity. Although no difference of lipid content was observed between PA0.5 and Ctrl groups, the lipid content was at a higher level in PA0.2 group than in the other three groups. Hence, concentration of 0.5 mM of PA was performed in the following experiments, and 2.5 μM AXE carried out to investigate the possible relief effects of PA (PA0.5 + AXE). Results showed that the percentage of matured oocytes with PB1 was higher in PA0.5 + AXE than in PA0.5 group (63.43% ± 1.50% vs. 55.33% ± 0.81%, p < .01), and ROS levels both in oocytes and their cumulus cells (CCs) reduced in PA0.5 + AXE when compared to PA0.5 group. In addition, the rate of CCs with apoptosis decreased in PA0.5 + AXE, and the expression level of caspase 3 and BAX was lower than PA0.5 group. In conclusion, the maturation of pig oocytes was inhibited by the high concentration of PA; however, this negative effect of PA‐induced might be relieved by the supplement of AXE.